2019
DOI: 10.1177/0020720919867437
|View full text |Cite
|
Sign up to set email alerts
|

Teaching internet of things for engineering courses: A project-based cooperative approach

Abstract: Internet of things is emerging in the recent years and is changing many traditional industries in the recent years. Engineering students of several knowledge areas may benefit with the introduction of internet of things concepts in the undergraduate courses, since there is an increasingly need of professionals to work in multidisciplinary teams. This paper proposes an undergraduate course to teach internet of things concepts for engineering students using cooperative problem-based learning (CPBL). The students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…nonlinear interaction between the elements, the whole component elements and, reveals the collaborative promotion mechanism innovation and entrepreneurship education system of colleges and universities. 18 and then promotes the development of innovation and Entrepreneurship system of colleges and universities by constructing, optimizing and adjusting the sequence evolution. In addition, from the perspective of ecosystem, 19 the ecosystem, organism and environment in a certain natural space are whole.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…nonlinear interaction between the elements, the whole component elements and, reveals the collaborative promotion mechanism innovation and entrepreneurship education system of colleges and universities. 18 and then promotes the development of innovation and Entrepreneurship system of colleges and universities by constructing, optimizing and adjusting the sequence evolution. In addition, from the perspective of ecosystem, 19 the ecosystem, organism and environment in a certain natural space are whole.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…In this respect, it can be said that the study supports the views of Keskin and Yurdugül (2022) and Tianbo (2012). In addition, the current study showed that IoT concepts and technical skills can be acquired by students from different engineering programs that constitute the study group, and similar results were obtained in the related studies (Kleinschmidt, 2021;.…”
Section: Conclusion and Suggestionssupporting
confidence: 81%
“…A limited number of studies on IoT education based on a specific curriculum and pedagogical approach were found in the literature, and it was observed that different learning methods were used in these studies. These learning methods commonly used for IoT education include problem-based learning (Mäenpää et al, 2017), project-based learning (Abraham, 2016;Ferreira et al, 2019;Kusmin, Saar, & Laanpere, 2018;Mäenpää et al, 2015;Nelke & Winokur, 2020;Rout et al, 2017), activity-based learning (Porter, Morgan, & Johnson, 2017), collaborative learning (Kortuem et al, 2013;Maiti, Byrne, & Kist, 2019;Plauska & Damaševičius, 2014), flipped learning (Gonçalves et al, 2020;, and some constructivist approaches (Charlton & Avramides, 2016;Kleinschmidt, 2021;Osipov & Riliskis, 2013;Ronoh et al, 2021). However, considering the multifaceted structure, interdisciplinary nature and complexity of IoT technology, it can be said that more research using different learning methods and tools is needed.…”
Section: Literaturementioning
confidence: 99%
“…IoT technologies are considered essential for learning in the field of sensors. Kleinschmidt [ 51 ] presented an undergraduate course teaching IoT concepts for engineering students using collaborative problem-based learning. The students develop a project using IoT technologies: sensors and actuators, embedded computing, communication and networking, cloud computing, and data analysis.…”
Section: Iot In Educationmentioning
confidence: 99%